2011
DOI: 10.1128/jcm.01475-10
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C Virus Infections in the Three Pygmy Groups in Cameroon

Abstract: A high (11.8%) level of hepatitis B virus (HBV) infection was found among 524 Pygmies in Cameroon, whereas the extent of hepatitis C virus (HCV) infection in the same population was low (0.6%). Phylogenetic analyses showed cocirculation of two HBV genotypes, HBV-A3 and -E. Taken together, our results suggest different epidemiological scenarios concerning HBV and HCV infections in this population.Sub-Saharan Africa is considered to be an area of high hepatitis B virus (HBV) and hepatitis C virus (HCV) endemicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
4
33
1
4
Order By: Relevance
“…To address the misclassification of HBV subgenotypes that lack enough nucleotide divergence and bootstrapping value to definitively be considered subgenotypes, we previously proposed the term of quasi-subgenotype [54] . This term has somewhat settled irregularities in subgenotyping of HBV and was respected by other studies [10,62,69,81,113,118,[139][140][141][142][143] . To address the classification of recombinant strains, which are being introduced as independent subgenotypes, we propose to call the indefinitely recombinant strains as "recombino-subgenotype" rather than an independent subgenotype.…”
Section: Proposing the Term "Recombino-subgenotype"mentioning
confidence: 91%
“…To address the misclassification of HBV subgenotypes that lack enough nucleotide divergence and bootstrapping value to definitively be considered subgenotypes, we previously proposed the term of quasi-subgenotype [54] . This term has somewhat settled irregularities in subgenotyping of HBV and was respected by other studies [10,62,69,81,113,118,[139][140][141][142][143] . To address the classification of recombinant strains, which are being introduced as independent subgenotypes, we propose to call the indefinitely recombinant strains as "recombino-subgenotype" rather than an independent subgenotype.…”
Section: Proposing the Term "Recombino-subgenotype"mentioning
confidence: 91%
“…In Cameroon, according to a review of literature published between 1985 and 2014 concerning studies on sentinel populations (blood donors, pregnant women, health workers, Pygmies), prevalence ranges between 6.1% and 25.3% [2] [3] for hepatitis B virus (HBV), and 0.6% and 21% for hepatitis C virus (HCV) [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, few HBV genotype studies have been conducted Central Africa. Makuwa et al reported the identification of HBV-A3 in rural Gabon [135], while this genotype is co-circulating with HBV-E among Pygmies in Cameroon [136]. More recently, a pilot study was conducted in the village of Dienga, Gabon (previously described in section 2.1) with the aim of looking at potential interactions between HBV, HCV and P. falciparum infections, which are all very prevalent in this region [137].…”
Section: Hepatitis Virusesmentioning
confidence: 99%